Types of speech style performed by the characters in birds of prey movie - Cahyani, Ni Made Diah; Utami, Ni Made Verayanti; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2021)
People speaking language differently, it can be influenced by some social factors. This research is intended to find out the kinds of speech style and the variables that influencing the characters of “Birds of Prey” in speaking a language. There are two aims of this study, those are: 1) To find out the kinds of speech style are used in “Birds of Prey” movie, 2) To find out the dominant style used by the character in “Birds of Prey” movie. This research is using descriptive qualitative method in analyzing the data with the theory proposed by Joos (1967) to divine the style of speech style. The result of the data was presented in both formal and informal method in finding presentation. The formal method was applied through table and the informal method was applied through word explanation to explain which type of an utterance belongs to. The result of this study showed there are 266 utterances that categorized into type of speech style, there are 4 types of speech style that grouped into: 17 formal styles, 56 consultative styles, 180 casual style and 13 intimate styles with casual style as the dominant style to be used by the character according to the movie’s rating and genre.